Gene therapy with VEGF 165 for angiogenesis in experimental acute myocardial infarction - Sant'Anna,Roberto T. (2003)
OBJECTIVE: Evaluate coronary angiogenic response to transmural injection of plasmid encoding VEGF 165 in acute myocardial infarction (AMI) zones in a canine model. METHODS: The heart of eleven dogs was exposed and AMI was induced by occlusion of the diagonal branch of anterior descending coronary artery. For each of 10 selected points in the infarction area and its peripheral zone injections of 1 ml of saline solution (control group: five dogs) or 1 ml of plasmid encoding VEGF 165 solution (200 µg/ml) (VEGF group: six dogs) were introduced. Tecnecium myocardial scintigraphy was performed immediately after animal recovery and 14 days later to evaluate the myocardial perfusion. The animals were sacrificed and the hearts were submitted to a histological study of the infarcted area, peripheral zone and normal posterior ventricular wall, to evaluate the number of arterioles and capillaries. RESULTS: Immediate modifications in myocardial perfusion found in scintigraphic studies were similar in both groups. In the second evaluation at 14 days, hypoperfusion of ischemic area had recovered by 70% to 90% when compared to the day of AMI. Histologic evaluation of the peripheral area of AMI indicated a larger number of vessels in the VEGF group when compared to controls (mean: 123.81 + 21.48 and 40 + 6.13, p < 0.01, respectively). This increase resulted mainly from an increase in the number of capillaries (97.5 + 16.04 in the VEGF group and 22.18 + 3,25 in control group, p < 0.01), as the number of arterioles did not increase significantly. In the VEGF group, a comparison in the number of vessels of the AMI peripheral area and normal myocardium revealed a non-significant increase of vessels in the ischemic area (123.81 + 21.48 and 95.14 + 41.19). CONCLUSION: An intramural injection of plasmid VEGF 165 resulted in a significant increase in the number of capillaries in the peripheral AMI area. This increase may have a beneficial effect in the reduction and recovery of the ischemic area secondary to AMI.